Using e-balanced scorecard in managing the performance and excellence academicians - Hamid, S.; Yu, M.L.; Soo, H.P.; Ijab, M.T. (2008)
The corporate performance and measurement discipline is dynamically changing. Organization will increasingly identify sets of performance issues and build tracking mechanisms to monitor how the enterprise is doing. As a practice, performance measurement and management requires objectivity and careful planning in order to see its successful, continuous implementation. University Malaya is currently looking at the balanced scorecard (BSC) as the performance measurement and management tool in assessing the whole spectrum of what defines an excellent organization. This study specifically researches the use of an electronic BSC system (e-BSC) in measuring the performance and excellence of academicians in University Malaya from the perspectives of Financial, Customer, Internal Business Process (IBP) and Learning and Growth (L&G). To substantiate this research work, a survey and several interviews were conducted. Graphs are presented to depict the user requirements of the development of the e-BSC System. Furthermore, based on the obtained information too, the performance measurement framework is proposed. The advantage of adopting an automated balanced scorecard to manage the performance of academicians is that it sanctions excellence and provides a platform for better organization-wide alignment of strategies. The demand for a better performance measurement system has thus far been proven through the findings obtained.